UTILIZATION OF FLY ASH FROM PLTU KETAPANG AS FILLER ON HOT ROLLED SHEET (HRS-Base) - Juanda, Rizky Hendarta; Azwansyah, Heri; Kadarini, S. Nurlaily; Erwan, Komala (Fakultas Teknik Universitas Tanjungpura, 2022)
The utilization of stone dust waste produced from PLTU Ketapang coal combustion process is still below optimal level. Produced waste reached ± 23,13 ton /day which consists of 99,5% of fly ash and 0,5% bottom ash. As a result, the writer gained an idea of using fly ash as a filler in bitumen mixture, especially in Hot Rolled Sheet